2017
DOI: 10.1017/s2045796017000579
|View full text |Cite
|
Sign up to set email alerts
|

Rising incidence of psychiatric disorders before diagnosis of immune-mediated inflammatory disease

Abstract: Aims. After the diagnosis of immune-mediated inflammatory diseases (IMID) such as inflammatory bowel disease (IBD), multiple sclerosis (MS) and rheumatoid arthritis (RA), the incidence of psychiatric comorbidity is increased relative to the general population. We aimed to determine whether the incidence of psychiatric disorders is increased in the 5 years before the diagnosis of IMID as compared with the general population.Methods. Using population-based administrative health data from the Canadian province of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 38 publications
(49 reference statements)
7
75
1
2
Order By: Relevance
“…These findings are consistent with available epidemiological evidence indicating that the presence of one set of disorders portends increased risk for a diagnosis from the other class of disorders, though the causality and temporality of these relationships is not clearly established. [76][77][78][79][80][81][82] Positive genetic inter-correlations among these phenotypes are also consistent with recent work demonstrating that the positive correlation between BD and SZ are significantly mediated by both CNS and immunologic tissues. 83 Our local genetic correlation analyses were inadequately powered to detect loci relevant to most of the psychiatric-immune disorder pairs, including BD.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with available epidemiological evidence indicating that the presence of one set of disorders portends increased risk for a diagnosis from the other class of disorders, though the causality and temporality of these relationships is not clearly established. [76][77][78][79][80][81][82] Positive genetic inter-correlations among these phenotypes are also consistent with recent work demonstrating that the positive correlation between BD and SZ are significantly mediated by both CNS and immunologic tissues. 83 Our local genetic correlation analyses were inadequately powered to detect loci relevant to most of the psychiatric-immune disorder pairs, including BD.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that, in addition to genetic and environmental factors, the onset and progression of schizophrenia are also linked to deficits in dopamine secretion in the endocrine and central nervous systems, as well as other immune mechanisms. 54,63 An extended psychiatric history has many drawbacks, such as loss of function, economic burden, family or work issues, diagnostic difficulties, relapse risk, or a general unwillingness to follow medical advice, again leading to elevated suicide risk. 64 In the present study, we observed a high risk of suicide in patients who developed psychiatric disorders after physical illness, which may reflect the failure to detect worsening of psychiatric symptoms following the onset of physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…− Such studies have indicated that patients with psychiatric disorders may experience worsening of cardiovascular diseases due to dysfunction of the HPA axis and autonomic nervous system, thereby leading to increased levels of cortisol, blood cholesterol (triglycerides), and blood pressure . Some studies have also indicated that psychiatric disorders are associated with platelet activation and dysregulation of the immunoinflammatory system, increasing the risk of cardio‐ and cerebrovascular diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve citations reported the incidence of psychotic disorders in a population group with a preexiting comorbidity and compared it with a general population cohort [27][28][29][30][31][32][33][34][35][36][37][38] . These studies are summarized in Table 6 below.…”
Section: Incidence Of Psychotic Disorders In Special Population Groupsmentioning
confidence: 99%